PENGARUH KREDIBILITAS SUMBER DALAM IKLAN SHAMPOO CLEAR MEN TERHADAP MINAT BELI KONSUMEN - Arga Mulya Purwandika, 10.05.51.0017; Soliha, Euis (Students Journal of Economic and Management, 2014)
This research is research that tested the influence of source credibility i.e. attractiveness, trustworthiness, and expertise in advertising shampoo Clear Men against the buying interest on Stikubank UniversityÂ of semarang, to see how much the influence of an endorser/source in ads can attract and raise interest in buying consumer. In this study, researchers used a pusposive sampling and sample size of 150 samples ofÂ students Stikubank University. Data from the questionnaire and then tested with validitas, Reliabilitas, Test hypotheses, and multiple regression. The result variable attractiveness, trustworthiness, and expertise influence on consumer buying interest. This study has limitations namely the sampling period is relatively short and just take sample of students Stikubank University. Therefore, further research on the period of time in considering recommend taking samples and wider use of samples and adding variables. Keywords: Atrractiveness, Trustworthiness, Expertise, and Buying Interests